STRATEGI KOMUNIKASI DA’WAH TGH. LALU MUCHSIN EFFENDI MUCHTAR MELALUI FORUM KERUKUNAN UMAT BERAGAMA (FKUB) DALAM MEWUJUDKAN KERUKUNAN BERAGAMA DI LOMBOK UTARA - Ujang Habibi; Lalu Burhan Lasende (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2024)
Research Objectives: Knowing Tgh. Lalu Muchsin Effendi Muchtar's Da'wah Communication Strategy Through FKUB in Creating Religious Harmony. Research Methods: Qualitative. Research Results: Tgh. Lalu. Muchsin Effendi Muchtar at FKUB in realizing religious harmony in North Lombok with various approaches and communication strategies to people who are not only Muslim. Conclusion: Tgh. Lalu Muchsin Muchtar himself uses a da'wah communication strategy, namely getting to know the audience: cross-religious discussions, cultural approaches, friendship between religious leaders, composing messages: conducting studies, seminars, providing exemplary and fiqhud da'wah approaches, establishing methods: deliberations and analysis These approaches were of course chosen after looking at the da'wah map of the North Lombok area, which is structurally very multi-cultural and multi-religious.